Zika Virus Impairs Neurogenesis and Synaptogenesis Pathways in Human Neural Stem Cells and Neurons - Rosa-Fernandes, Livia; Cugola, Fernanda Rodrigues; Russo, Fabiele Baldino; Kawahara, Rebeca; de Melo Freire, Caio Cesar; Leite, Paulo Emílio Corrêa; Bassi Stern, Ana Carolina; Angeli, Claudia Blanes; de Oliveira, Danielle Bruna Leal; Melo, Stella Rezende; Zanotto, Paolo Marinho de Andrade; Durigon, Edison Luiz; et al. (Frontiers in Cellular Neuroscience, 2019)
Growing evidence has associated Zika virus (ZIKV) infection with congenital malformations, including microcephaly. Nonetheless, signaling mechanisms that promote the disease outcome are far from being understood, affecting the development of suitable therapeutics. In this study, we applied shotgun mass spectrometry (MS)-based proteomics combined with cell biology approaches to characterize altered molecular pathways on human neuroprogenitor cells (NPC) and neurons derived from induced pluripotent stem cells infected by ZIKV-BR strain, obtained from the 2015 Brazilian outbreak. Furthermore, ZIKV-BR infected NPCs showed unique alteration of pathways involved in neurological diseases, cell death and survival and embryonic development compared to ZIKV-AF, showing a human adaptation of the Brazilian viral strain. Besides, infected neurons differentiated from NPC presented an impairment of neurogenesis and synaptogenesis processes. Taken together, these data explain CNS developmental arrest observed in Congenital Zika Syndrome is beyond neuronal cell death.